An Exploration of Artificiality. Issue 1 (1st March 2007) - Krippendorff, Klaus
The following explores the artificiality of human artifacts. To talk of artifacts, we must avoid ontologizing. Ontology ignores human participation in its construction and describing artifacts as if their descriptions had nothing to do with it contradicts the idea of their artificiality. Instead, I will explore the nature of artifacts from the perspective of human-centered design and with culture-sensitive conceptions in mind. Exploring artifacts from this perspective offers scholars and practitioners a fascinating field of inquiry. To follow are six closely connected mini essays on artifacts, starting with the use of the word ''artifact'' and ending with the virtual worlds that artifacts can bring forth.